Enhancing symbolic system synthesis through ASPmT with partial assignment evaluation - Neubauer, Kai; Wanko, Philipp; Schaub, Torsten; Haubelt, Christian (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2017)
The design of embedded systems is becoming continuously more complex such that efficient system-level design methods are becoming crucial. Recently, combined Answer Set Programming (ASP) and Quantifier Free Integer Difference Logic (QF-IDL) solving has been shown to be a promising approach in system synthesis. However, this approach still has several restrictions limiting its applicability. In the paper at hand, we propose a novel ASP modulo Theories (ASPmT) system synthesis approach, which (i) supports more sophisticated system models, (ii) tightly integrates the QF-IDL solving into the ASP solving, and (iii) makes use of partial assignment checking. As a result, more realistic systems are considered and an early exclusion of infeasible solutions improves the entire system synthesis.